2020
DOI: 10.5888/pcd17.190367
|View full text |Cite
|
Sign up to set email alerts
|

Pain Among Cancer Survivors

Abstract: Introduction Pain is one of the most common symptoms that people with cancer experience. Identification of demographic, physiologic, and behavioral correlates of pain among cancer survivors could help identify subgroups most in need of pain management. Methods We analyzed data from the 2012, 2014, and 2016 Behavioral Risk Factor Surveillance System Cancer Survivorship Optional Module, which was completed by 18 states and territories, to describe demographic and physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 25 publications
1
32
1
Order By: Relevance
“…Younger patients reported both more frequently CRP and also higher pain severity than older patients which is consistent with previous studies [e.g., ( 15 )]. Gallaway et al ( 46 ) found that cancer survivors older than 65 reported pain less frequently. Another study similarly found that younger age was associated with higher risk for pain in breast cancer survivors ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Younger patients reported both more frequently CRP and also higher pain severity than older patients which is consistent with previous studies [e.g., ( 15 )]. Gallaway et al ( 46 ) found that cancer survivors older than 65 reported pain less frequently. Another study similarly found that younger age was associated with higher risk for pain in breast cancer survivors ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research is needed to determine the effectiveness of art therapy in reducing psychological distress related to cancer and its treatment, and alleviating pain and its impact on quality of life. With more knowledge, there is hope for patients to receive more effective and efficient pain management while going through treatment 9. When a patient's pain is managed, the patient is less likely to end up in the hospital with extreme episodes of pain.…”
Section: Background and Significancementioning
confidence: 99%
“…According to the Centers for Disease Control and Prevention, 8 pain is a symptom of cancer and a side effect of many treatments, surgeries, procedures, and tests performed throughout a patient's treatment and recovery. 9 Daily living activities can be affected by the frequent or constant pain often experienced by patients undergoing treatments. 10 Due to this, scientists and medical professionals are leaning more toward complementary care when treating conditions such as cancer.…”
Section: Background and Significancementioning
confidence: 99%
“…With more knowledge, there is hope for patients to receive more effective and efficient pain management while going through treatment. 9 When a patient's pain is managed, the patient is less likely to end up in the hospital with extreme episodes of pain.…”
Section: Background and Significancementioning
confidence: 99%